A Replication of Macchi (2023): "Worth Your Weight: Experimental Evidence on the Benefits of Obesity in Low-Income Countries" - Melchior Clerc; Adrien Gosselin-Pali; Eliot Wendling (Institute for Replication (I4R), 2024)
Elisa Macchi (2023) investigates the impact of obesity on the perceived wealth of individuals using primary data collected in Kampala, Uganda. The study includes two complementary experiments: a beliefs experiment and a credit experiment. In the beliefs experiment, individuals assess the wealth of others based on weight-manipulated portraits, while in the credit experiment, loan officers evaluate creditworthiness using similar portraits. In this paper, we reproduce the author's results using the freely accessible replication package. Additionally, we test the robustness of the findings by (1) proposing different nutritional status categorizations, (2) applying alternative estimation strategies via ordered probit/logit models, (3) using different levels of clustering, and (4) excluding extreme values. Overall, our findings supports the main conclusions of the original paper.
Keywords: 330